Brazil's Balbina Dam: Environment versus the legacy of the Pharaohs in Amazonia - Fearnside, Philip Martin (Environmental Management, 1989)
The Balbina Dam in Brazil's state of Amazonas floods 2360 km2 of tropical forest to generate an average of only 112.2 MW of electricity. The flat topography and small size of the drainage basin make output small. Vegetation has been left to decompose in the reservoir, resulting in acidic, anoxic water that will corrode the turbines. The shallow reservoir contains 1500 islands and innumerable stagnant bays where the water's residence time will be even longer than the average time of over one year. Balbina was built to supply electricity to Manaus, a city that has grown so much while the dam was under construction that other alternatives are already needed. Government subsidies explain the explosive growth, including Brazil's unified tariff for electricity. Alternative power sources for Manaus include transmission from more distant dams or from recently discovered oil and natural gas deposits. Among Balbina's impacts are loss of potential use of the forest and displacement of about one third of the surviving members of a much-persecuted Amerindian tribe: the Waimiri-Atroari. The dam was closed on 1 October 1987 and the first of five generators began operation in February 1989. The example of Balbina points to important ways that the decision-making process could be improved in Brazil and in the international funding agencies that have directly and indirectly contributed to the project. Environmental impact analyses must be completed prior to decisions on overall project implementation and must be free of influence from project proponents. The current environmental impact assessment system in Brazil, as in many other countries, has an undesirable influence on science policy, in addition to failing to address the underlying causes of environmentally destructive development processes and inability to halt "irreversible" projects like Balbina. © 1989 Springer-Verlag New York Inc.
Keywords: Dam; Decision Making Process; Electricity Generation; Environmental Impact Analysis; Environmental Impact Assessment; Hydroelectricity; Indigenous People; Tropical Forest; Brazil, Amazonas State, Balbina Dam; Brazil, Amazonia, Balbina Dam; Brazil, Manaus; Environmental Engineering; Hydroelectric Power Plants--environmental Impact; Water Pollution--analysis; Balbina Dam; Dams; Decision Making; Economic Aspect; Electric Power Plant; Environmental Impact Assessment; Environmental Planning; Ethnic Or Racial Aspects; Human; Legal Aspect; Organization And Management; Reservoir; Review; Water Management